Use of patient flow analysis to improve patient visit efficiency by decreasing wait time in a primary care-based disease management programs for anticoagulation and chronic pain: a quality improvement study - Shilliday Betsy; Malone Robb M; Potisek Nicholas M; Ives Timothy J; Chelminski Paul R; DeWalt Darren A; Pignone Michael P (BMC, 2007)
Abstract Background Patients with chronic conditions require frequent care visits. Problems can arise during several parts of the patient visit that decrease efficiency, making it difficult to effectively care for high volumes of patients. The purpose of the study is to test a method to improve patient visit efficiency. Methods We used Patient Flow Analysis to identify inefficiencies in the patient visit, suggest areas for improvement, and test the effectiveness of clinic interventions. Results At baseline, the mean visit time for 93 anticoagulation clinic patient visits was 84 minutes (+/- 50 minutes) and the mean visit time for 25 chronic pain clinic patient visits was 65 minutes (+/- 21 minutes). Based on these data, we identified specific areas of inefficiency and developed interventions to decrease the mean time of the patient visit. After interventions, follow-up data found the mean visit time was reduced to 59 minutes (+/-25 minutes) for the anticoagulation clinic, a time decrease of 25 minutes (t-test 39%; p < 0.001). Mean visit time for the chronic pain clinic was reduced to 43 minutes (+/- 14 minutes) a time decrease of 22 minutes (t-test 34 %; p < 0.001). Conclusion Patient Flow Analysis is an effective technique to identify inefficiencies in the patient visit and efficiently collect patient flow data. Once inefficiencies are identified they can be improved through brief interventions.